Analisis Minat Karier Berdasarkan Teori Karier Holland Siswa Sekolah Menengah Pertama di Kabupaten Gresik - Mudhar, Mudhar; Hasiana, Isabella; Mufidah, Elia Firda; Badiah, Lutfi Isni (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
This study aims to analyze the career interests of junior high school students in the city of Gresik. Data collection used career interest instruments based on Holland's career theory (RIASEC) which was then developed by researchers. This research uses descriptive quantitative research. Sampling used random sampling of 476 students in SMPN Gresik city area (Sunan Giri Gresik Middle School with 88 students, Gresik 2nd Middle School with 298 students, and Gresik 15th Middle School with 90 students). The research instrument was tested for the validation and reliability of Cronbach's alpha. The results showed that the career personality type of junior high school students in Gresik district was the highest, namely the social career personality type, which was 32.8%. Next, namely the career personality type towards the conventional type as much as 18.7%. As many as 14.9% of junior high school students in Gresik district have a realistic career personality type. As many as 11.1% of junior high school students in Gresik district have the investigative career personality type. 12% of junior high school students in Gresik Regency and 10.5% of students have artistic career personality types.